Characterization of hopanes in sediment collected from South China Sea: identification of oil pollution sources - Ismail, Norliza; Zakaria, Mohamad Pauzi; Abdullah, Abdul Halim (2009)
This study investigate the utilities and limitation of pentacyclic triterpane (hopane) including oleanane as oil pollution source identification for sediment samples collected from South China Sea and the applicability of the biomarker approach to sediments and biological samples. Norhopane, 17(α),21(β)-hopane and 17(β), 21(α)-hopane and ∑C31-C 35-homohopane were found to be rich in Middle East crude oil and some of the sediment samples that were being collected in South China Sea. Some other molecular ratios of the biomarker compounds for the sediments such as Tm/Ts and Ts/Tm and n-alkane composition and distribution strongly suggest those 3 out of 27 sediment samples are derived from the Middle East petroleum. The utility of hopane as biomarker to identify the source of tar balls in Strait of Malacca is applicable for oil spill but the data is still limited for Malaysian sediments especially in South China Sea area. The use of oleanane as a biomarker is easily to be found in each sample for this study; however the concentration generally was very low for each sediment sample.